Depletion of gamma interferon and tumor necrosis factor alpha in mice with Rickettsia conorii-infected endothelium: impairment of rickettsicidal nitric oxide production resulting in fatal, overwhelming rickettsial disease. - Feng, H M (1994)
C3H/HeN mice infected intravenously with a dose of Rickettsia conorii (Malish 7 strain) that is sublethal for immunocompetent animals (1.1 x 10(3) PFU) developed disseminated infection of endothelial cells of the brain, lungs, heart, liver, kidney, testis, and testicular adnexa. In R. conorii-infected mice depleted of gamma interferon (IFN-gamma) and/or tumor necrosis factor alpha (TNF-alpha) by intravenous administration of neutralizing monoclonal antibodies on days 0, 2, and 4, the mortality rate was 100%. Death of the cytokine-depleted animals on days 5 and 6 was associated with overwhelming rickettsial infection documented by titration of rickettsial content in the brain and liver and by immunohistologic demonstration of massive quantities of R. conorii in endothelial cells of all organs examined, in macrophages of the liver and spleen, and in hepatocytes. Nondepleted, immunocompetent animals showed markedly reduced rickettsial content in the tissues on day 6, with rickettsial destruction in phagolysosomes not only in macrophages but also in endothelial cells and hepatocytes. All nondepleted, infected mice recovered and appeared completely healthy by day 9. Assay of liver infiltrated by lymphocytes and macrophages revealed mRNA of IFN-gamma and TNF-alpha, indicating that the host defenses were activated at the site of infection. Treatment of mice with an analog of L-arginine reduced the synthesis of nitric oxide and impaired rickettsial killing. Nitric oxide production was also impaired in cytokine-depleted infected mice. These observations support the hypothesis that IFN-gamma secreted by T lymphocytes and natural killer cells and TNF-alpha secreted by macrophages act in a synergistic, paracrine fashion on adjacent rickettsia-infected endothelial cells, hepatocytes, and macrophages to stimulate synthesis of nitric oxide, which kills intracellular R. conorii.